Evaluating the Impact of Posterior Pericardiotomy on Early Postoperative Outcomes in Valve Surgery Patients - Barira Ahmad, Waqas Hamid, Muhammad Ali Khan, Muhammad Moeen (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: to evaluate the early outcomes of posterior pericardiotomy in patients undergoing heart valve surgery, with a focus on reducing the incidence of postoperative atrial fibrillation (AF), pericardial effusion (PE). Study Setting: This study was conducted at Cardiac Surgery Department, Chaudhary Pervaiz Elahi Institute of Cardiology, Multan, from January 2023 to July 2023. Methods: A total of 150 patients undergoing elective valve heart surgery at Chaudhary Pervaiz Elahi Institute of Cardiology, Multan, were included in this prospective observational study. The mean age of patients was 35.26 years, with a gender distribution of 70.2% female and 29.8% male. Patients were followed up for postoperative complications, including AF, PE, and tamponade requiring intervention. ICU and total hospital stay durations were recorded and analyzed based on the presence of complications. Results: Among 150 patients undergoing posterior pericardiotomy (PP) during elective heart valve surgery, the incidence of postoperative atrial fibrillation (POAF) was 4% (6 patients), with no significant association with age, gender, smoking, or residential status (p > 0.05). Pericardial effusion occurred in 2% (3 patients) but needs no drainage, predominantly in smokers, although this was not statistically significant (p = 0.121). The mean ICU stay was 1.82 ± 0.54 days, and the mean hospital stay was 5.06 ± 0.99 days. No cases of cardiac tamponade or significant pericardial effusion requiring intervention were observed. These findings suggest that PP may contribute to a low incidence of early postoperative complications in heart valve surgery patients. Conclusion: Posterior pericardiotomy is a safe and effective procedure that can significantly reduce the incidence of postoperative AF, PE, and left pleural effusion following valve heart surgery. The procedure is associated with shorter ICU and hospital stays in patients without complications, contributing to improved postoperative outcomes. Keywords: Posterior pericardiotomy, Heart valve surgery, Postoperative atrial fibrillation, Pericardial effusion, Early outcomes.